Tinjauan Yuridis Perjanjian Kerja Sama Sampoerna Retail Community Antara PT Hanjaya Mandala Sampoerna Dengan Toko Najwa di Wilayah Kecamatan Kampar Timur Ditinjau dari Perspektif Hukum Anti Monopoli dan Persaingan Usaha Tidak Sehat - Maida Wahyuni; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cooperation agreement conducted by PT. Hanjaya Mandala Sampoerna with the najwa store hascreated rights and obligations that must be carried out by both parties, but in reality one party, namely theshop owner Najwa defaulted or did not carry out the cooperation agreement well. how the rights andobligations in the cooperation agreement Second, knowing how the violations committed by the shop owner,and the Third knowing the efforts made by PT. Hanjaya Mandala Sampoerna in completing the breachcarried out by Najwa shop ownersThis type of research can be classified in types of sociological research, because in this study theauthors direct research on the location or place a complete thorough in order to give a complete and clearpicture of the problems researched.From the results of this study the authors concluded, First, that in the implementation of thecooperation agreement carried out by PT. Hanjaya Mandala Sampoerna with the Najwa store, it had notbeen implemented properly, as seen from the default carried out by Najwa shop owners such as sellingsmuggled cigarettes, removing promotional material without the knowledge and permission of Sampoerna'sagent, and not arranging cigarettes at the cigarette display provided by the agent in accordance with theprovisions of the agent. Second, the efforts made by the agent in resolving the default that is carried out bythe store are to give a warning and if the warning is ignored, the agent has the right to terminate the workand retrieve all promotional media and facilities provided by Sampoerna and the store is also processedbased on the legal and regulatory provisions that apply in the Republic of Indonesia because they have soldsmuggled cigarettes.Keywords : cooperation agreement-default